The communicative status of clauses with pero: an analysis from the perspective of Functional Discourse Grammar - da Costa Pedro, Carolina [UNESP]; Garcia, Talita Storti [UNESP] (Universidade Estadual de Maringa, 2021)
This article aims to investigate, from the perspective of Functional Discourse Grammar (Hengeveld y Mackenzie, 2008), the functional motivations of clauses introduced by ‘pero’ and to discuss the communicative status of the clauses introduced by that conjunction. According to Hengeveld and Mackenzie (2008), ‘but’ [‘pero’] acts between two Discursive Acts with a different status, in which one is Subsidiary, the one presenting the rhetorical function Concession (Conc), and the other, Nuclear. This means that the Nuclear Act, from the Speaker's point of view, contains the most important communicative information. This distinction is encoded at the Morphosyntactic Level, with the Grammatical Word ‘pero’. The results show that the uses of ‘pero’ show pragmatic purposes. The data shows that pero acts at the highest levels of the Interpersonal Level, the Discursive Act, and the Movement. When it acts between two Discursive Acts, the second one present the most important content. This finding coincides with the great argumentative value of ‘but’ recognized by Anscombre and Ducrot (1977) from the point of view of argumentation. The research universe is the PRESEEA corpus (Project for the study of Spanish in Spain and America [PRESEEA], 2014), with examples from the cities of Granada and Alcalá de Henares, in Spain.
El estatuto comunicativo de cláusulas con pero: un análisis desde la perspectiva de la Gramática Discursivo-Funcional
Keywords: Adversatives; Argumentation; Functionalism; Pero